1999
DOI: 10.1002/biof.5520090238
|View full text |Cite
|
Sign up to set email alerts
|

Coenzyme Q10, a cutaneous antioxidant and energizer

Abstract: The processes of aging and photoaging are associated with an increase in cellular oxidation. This may be in part due to a decline in the levels of the endogenous cellular antioxidant coenzyme Q10 (ubiquinone, CoQ10). Therefore, we have investigated whether topical application of CoQ10 has the beneficial effect of preventing photoaging. We were able to demonstrate that CoQ10 penetrated into the viable layers of the epidermis and reduce the level of oxidation measured by weak photon emission. Furthermore, a redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
112
0
5

Year Published

2001
2001
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 221 publications
(123 citation statements)
references
References 29 publications
4
112
0
5
Order By: Relevance
“…After the age of 35, the organism begins to lose its ability to synthesise CoQ 10 from food and its deficiency develops (Hojerová 2000). Hoppe et al (1999) estimated CoQ 10 increases in the skin of the human skin from childhood to maturity and then decreases with age and under irradiation with UVA rays. Therefore, oral supplementation with CoQ 10 may be very helpful for the skin health.…”
Section: Topical Supplementmentioning
confidence: 95%
See 1 more Smart Citation
“…After the age of 35, the organism begins to lose its ability to synthesise CoQ 10 from food and its deficiency develops (Hojerová 2000). Hoppe et al (1999) estimated CoQ 10 increases in the skin of the human skin from childhood to maturity and then decreases with age and under irradiation with UVA rays. Therefore, oral supplementation with CoQ 10 may be very helpful for the skin health.…”
Section: Topical Supplementmentioning
confidence: 95%
“…Another direct demonstration of the elimination of free radicals is shown by coenzyme Q treatment of skin in elderly subjects. Luminescence is eliminated from free radicals when a skin cream containing coenzyme Q is applied (Hoppe et al 1999).…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…and 3 ('Did your erection last long enough for you to have successful intercourse?'). EF was categorized as follows using the IIEF-5 total scores: no ED (22)(23)(24)(25), mild ED (17-21), mild to moderate ED (12)(13)(14)(15)(16), moderate ED (8-11) and severe ED (5-7). 19,20 Presence and severity of painful erections was determined on a conventional 10-point visual analog pain scale (VAS) score ranging from 0 to 10, with 0 being no pain and 10 being severe pain.…”
Section: Evaluationsmentioning
confidence: 99%
“…CoQ 10 is one of the most potent antioxidants, which is used to regenerate other antioxidants (tocopheryl and ascorbate), and may serve important roles in protection against oxidative stress and free radical oxygen damage. 15 TGF-b1 is a key fibrogenic mediator. It has been reported that solubilized CoQ 10 suppresses the expression of TGF-b1 induced by dimethylnitrosamine in mouse liver and mouse embryonic fibroblast cells.…”
Section: Introductionmentioning
confidence: 99%
“…Since healthy individuals are able to synthesize CoQ 10 , it is not clear whether additional levels of CoQ 10 are beneficial. However, it has been reported that the level of CoQ 10 begins to decline in the skin at the age of 20 years and by the age of 40 years the level is reduced by at least 25% (4).…”
mentioning
confidence: 98%